From ritual to refuse faunal exploitation by the elite of Chinikiha, Chiapas, during the late classic period. - MONTERO LOPEZ, CORAL (ARCHAEOPRESS ARCHAEOLOGY, 2022)
From Ritual to Refuse explores the faunal exploitation by the Maya elite at the site of Chinikihá, Chiapas, during the end of the Late Classic period (AD 700-850) by applying zooarchaeological and statistical analyses to a faunal assemblage located in a basurero or midden behind a palatial structure at the core of the site. This deposit has been interpreted as the result of one or various feasting events. The aim is to investigate temporal changes of function, more specifically during periods of increasing political competitiveness. Moreover, these analyses suggest that there is a change in the use of faunal resources, from a ritual pattern to a more general refuse deposit. The results from the zooarchaeological analysis are supported by a dietary analysis using ?13C and ?15N stable isotopes conducted on human and faunal samples. The results from the faunal assemblage suggest that there was a constant supply of animals for ritual and non-ritual uses, and that these animals were mostly obtained in the wild.